PO124 Validation of an environmentally-friendly and affordable cardboard 9-hole peg test. (1st December 2017) - Dubuisson, Nicolas; Bauer, Angelika; Marta, Monica; Gnanapavan, Sharmilee; Turner, Benjamin; Baker, David; Giovannoni, Gavin; Schmierer, Klaus; Thomson, Alison
Abstract : Background: In multiple sclerosis (MS) upper limb neurological impairments, are an important driver of disability and handicap. The gold standard for assessing upper limb function is the 9-hole peg test (9HPT). One disadvantage of the current plastic version is its price, which prevents its widespread adoption by the MS community. Objective: To develop and validate an affordable 9HPT for patients to self-monitor upper limb function. Methods: We enrolled 177 volunteers, 68 healthy controls and 109 people with MS (pwMS) at varying stages of their disease. Volunteers performed two trials of the 9HPT with their dominant hand and two with their non-dominant hand using both plastic 9HPT and cardboard 9HPT. The primary comparison parameter was the time needed to perform the task. Results: The mean score for the cardboard 9HPT was 24.58 (SEM 1.54 s) seconds compared to 26.03 (SEM 1.44 s) seconds for the plastic 9HPT (p=0.007). However, the two versions of the tests correlated very strongly, r=0.96 (p<0.001). The coefficient of variation, repeat-repeat testing, showed less variability with the cardboard version than in the plastic one with 10% and 14%, respectively. Two-thirds of pwMS preferred using the cardboard version. Conclusion: This study demonstrates that the cardboard version is at least equivalent to the plastic version of the test with arguably better design attributes making it the preferred option for self-monitoring.